Rapidity gap cross sections measured with the ATLAS detector in pp collisions at √s=7 TeV - Aad, Georges; Anders, Gabriel; Andrei, George Victor; Davygora, Yuriy; Dietzsch, Thorsten; Geweniger, Christoph; Hanke, Paul; Henke, Michael; Khomich, Andrei; Kluge, Eike-Erik; Kugel, Andreas; Männer, Reinhard; et al. (The European physical journal. C, Particles and fields, 2012)
Pseudorapidity gap distributions in proton-proton collisions at s√=7 ~TeVs=7 ~TeV\sqrt {s} =7~~TeV are studied using a minimum bias data sample with an integrated luminosity of 7.1 μb−1. Cross sections are measured differentially in terms of Δη F , the larger of the pseudorapidity regions extending to the limits of the ATLAS sensitivity, at η=±4.9, in which no final state particles are produced above a transverse momentum threshold pcutTpTcutp_{T}^{cut}. The measurements span the region 0<Δη F <8 for 200~MeV<pcutT<800~MeV200~MeV<pTcut<800~MeV200 ~MeV< p_{T}^{cut} < 800 ~MeV. At small Δη F , the data test the reliability of hadronisation models in describing rapidity and transverse momentum fluctuations in final state particle production. The measurements at larger gap sizes are dominated by contributions from the single diffractive dissociation process (pp→Xp), enhanced by double dissociation (pp→XY) where the invariant mass of the lighter of the two dissociation systems satisfies M Y ≲7 GeV. The resulting cross section is dσ/dΔη F ≈1 mb for Δη F ≳3. The large rapidity gap data are used to constrain the value of the Pomeron intercept appropriate to triple Regge models of soft diffraction. The cross section integrated over all gap sizes is compared with other LHC inelastic cross section measurements.
The ATLAS Collaboration: G. Aad, G. Anders, V. Andrei, Y. Davygora, T.A. Dietzsch, C. Geweniger, P. Hanke, M. Henke, A. Khomich, E.-E. Kluge, A. Kugel, R. Maenner, K. Meier, F. Müller, R. Narayan, S. Poddar, S. Schaetzel, V. Scharf, A. Schöning, S. Schmitt, N. Schroer, H.-C. Schultz-Coulon, R. Stamen, M. Wessels [und weitere]
Gesehen am 29.11.2018